Dokuczliwy skrzyp hermeneutycznego koła – komentarz do artykułu Andrzeja Szahaja - Szajnert, Danuta (Przestrzenie Teorii, 2013)
This essay is merely an additional commentary on the article entitled “Hirsch o interpretacji. Analiza krytyczna” (“Hirsch on interpretation. A critical analysis”). I do not focus here on Szahaj’s detailed objections to the concepts proposed by the author of Validity in Interpretation. I concentrate instead on the idea that forms the basis for such objections, i.e. radical, cultural interpretative constructivism. As a skeptical intentionalist, I cannot fully share his opinion and, therefore, I draw attention to views according to which the constructivist paradigm is becoming conventionalized and exhausted (especially in the humanities) and to the possible ways in which it can be overcome.